2017
DOI: 10.1021/acs.biochem.7b00619
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for Biguanide Activity

Abstract: Metformin is the most commonly prescribed treatment for Type II diabetes and related disorders, however molecular insights into its mode(s) of action have been limited by an absence of structural data. Structural considerations along with an increasing body of literature demonstrating its effects on one-carbon metabolism suggest the possibility of folate mimicry and anti-folate activity. Motivated by increasing recognition that anti-diabetic biguanides may act directly upon the gut microbiome, we have determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 89 publications
2
39
0
Order By: Relevance
“…It is very likely the key to our success of obtaining the chemically labile FH4 complex structure is the timely harvesting of well diffracting crystals within 2 days’ growth under the crystallization condition identified here. In addition, a survey of the DHFR field indicates that many crystallographic 19,20,24,28,29,32,43,45,47,48,5052 and NMR 12,13,15,17,19,25,26 studies of DHFR applied dialysis to remove endogenous ligands before introducing the exogenous ligands of interest. We identified a crystallization condition that isolates the endogenous FH4-bound DHFR complex without dialysis of the protein sample or introduction of additional substrates or products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very likely the key to our success of obtaining the chemically labile FH4 complex structure is the timely harvesting of well diffracting crystals within 2 days’ growth under the crystallization condition identified here. In addition, a survey of the DHFR field indicates that many crystallographic 19,20,24,28,29,32,43,45,47,48,5052 and NMR 12,13,15,17,19,25,26 studies of DHFR applied dialysis to remove endogenous ligands before introducing the exogenous ligands of interest. We identified a crystallization condition that isolates the endogenous FH4-bound DHFR complex without dialysis of the protein sample or introduction of additional substrates or products.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray crystallography shows that the complex of eDHFR with a slow-onset tight inhibitor AMPQD 46 also displays the occluded conformation. The Met20 loop adopted a conformation in the AMPQD complex that resembles that of the ternary complex with an anti-diabetic biguanide phenformin and NADP + (PDB ID: 5UIH) 52 . On the other hand, the FDA-approved chemotherapeutic agent methotrexate was previously demonstrated by X-ray crystallography 24,47 , NMR 48 , and single-molecule kinetics 49 to bind in the closed DHFR conformation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the mechanisms of action of biguanides are not clearly understood, their oral administration probably have both direct and indirect effects on gut bacteria. It has notably been shown that metformin impairs folate metabolism in Escherichia coli [ 53 ], possibly by the inhibition of the dihydrofolate reductase activity [ 54 ]. In vitro, metformin is able to promote the growth of Akkermansia muciniphila and B. adolescentis , which indicates that this drug may be a growth factor for some bacterial species [ 20 , 26 ].…”
Section: The Effects Of Antidiabetic Treatments On Gut Microbiota mentioning
confidence: 99%
“…Antifolates, a group of anti-cancer agents targeting various enzymatic steps in folate-dependent 1C metabolism, are known to exert an indirect influence on the rate of appearance/disappearance of homocysteine from cellular and plasma/serum compartments [4246]. The ability of homocysteine to behave as a shared marker of the pharmacodynamic effect of metformin and antifolate drugs strongly supports the increasing recognition that anti-diabetic biguanides may exhibit folate mimicry and antifolate-like activity [2729,46]. Homocysteine levels are known to increase in non-cancer patients undergoing biguanide treatment [47,48], and metabolomic parallelisms have been noted between the responses of cancer cells to biguanides and anti-folate drugs such as methotrexate [27,49].…”
Section: Discussionmentioning
confidence: 99%